JHMN 2019
DOI: 10.7176/jhmn/68-10
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Muscles Stretching Exercises on Severity of Restless Legs Syndrome of Adult Patients Undergoing Hemodialysis

Abstract: The patients undergoing hemodialysis usually have several complications including restless leg syndrome, which is a neurological disorder characterized by uncomfortable sensation of paraesthesia in legs that subsequently causes involuntary and continuous movement of the lower limbs especially in night which can lead to; sleep disorder, anxiety, fatigue, depression, disturbance of ability to work and social isolation. Moderate exercise may be helpful in relieving restless leg syndrome. The aim of the study is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
1
0
0
Order By: Relevance
“…In relation to duration of the session, the present study revealed that most of the patients receiving HD session for four hours. This result was similar to Algendy & Bahgat, (2019) et al, (2021), who concluded that the study participants had moderate to severe muscle cramps during the HD procedure, but after application of exercise, a significant reduction in the severity of muscle cramps had been reported. This result signifies the effectiveness of intradialytic stretching exercises.…”
Section: Effect Of Intradialytic Stretching Exercises On Muscle Cramp...supporting
confidence: 91%
“…In relation to duration of the session, the present study revealed that most of the patients receiving HD session for four hours. This result was similar to Algendy & Bahgat, (2019) et al, (2021), who concluded that the study participants had moderate to severe muscle cramps during the HD procedure, but after application of exercise, a significant reduction in the severity of muscle cramps had been reported. This result signifies the effectiveness of intradialytic stretching exercises.…”
Section: Effect Of Intradialytic Stretching Exercises On Muscle Cramp...supporting
confidence: 91%